Life after Medicine: A Systematic Review of Studies of Physicians' Adjustment to Retirement - Michelle Pannor Silver; Angela D Hamilton; Aviroop Biswas; Sarah A Williams (Archives of Community Medicine and Public Health - Peertechz Publications, 2016)
Background: A physician's decision to retire has personal and social consequences. While there has been growing interest in how individuals adjust to retirement, less is known about physicians' adjustment to retirement. Objectives: To identify and examine: 1) factors that influence how well physicians adjust to retirement, 2) reasons physicians give for retiring; and 3) advice physicians give for a successful adjustment to retirement. Methods: A systematic review of the literature was performed by searching Medline, Web of Science, Scopus, CINAHL, Ageline, Embase, Health star, ASSA, and PsycINFO databases for peerreviewed studies published with quantitative and/or qualitative analyses of physicians' adjustment to, satisfaction with, and/or quality of life in retirement. Two independent reviewers performed data abstraction, a quality assessment and an additional reviewer resolved inconsistencies. Content analysis was used to identify and stratify information from selected studies into themes and subthemes. Results: Based on analyses of 12 articles that met the eligibility criteria, it is evident that retirement from medicine was seen as a generally favorable phenomenon. Financial security, favorable health, ngagement in activities, and psychosocial well-being were identified as key factors relevant to physician retirement adjustment. Findings suggest that physicians' retirement transitions could be eased by a greater focus on financial planning, implementation of strategies to encourage the development of outside interests, and institutional retirement planning that honors the physician and takes place mid-career or well in advance of retirement. Conclusions:  Advance planning to ensure that physicians have a strong financial situation, good health, engagement in activities outside of medicine, and positive psychosocial dynamics are likely to enhance adjustment to retirement for physicians. Future studies should account for multiple interrelating factors such as gender, changes over time, and spousal retirement to further enhance our understanding of physicians' adjustment to retirement.